Comparação da flexibilidade e resistência muscular localizada de adolescentes em diferentes picos de velocidade de crescimento - Silva, Filipe Ferreira; Queiroga, Marcos Roberto [UNESP]; de Souza, William Cordeiro; de Souza, Wallace Bruno; de Lima, Valderi Abreu; Mascarenhas, Luis Paulo Gomes (My University, 2017)
Objective: Compare the flexibility and muscular endurance of adolescents in different peak growth rate. Methods: 131 male adolescents participated had between 10 to 15 years. The subjects were divided into three groups according to the calculus of its peak growth rate (PGR). To evaluate the anthropometric variables, were collected body weight, height, leg length and body-head height. For the realization of the physical fitness tests, the sit and reach (flexibility) and the push-up test (muscular endurance) tests were performed. Data normality were verified through the Kolmogorov-Smirnov test. In the data comparison we used the analysis of variance: ANOVA One Way and post hoc Tukey to determine the differences between the groups. Results: The group after PGR showed significant differences to the group before PGR in the anthropometric variables. In regards to flexibility variable, no significant differences were found between the groups. The variable muscular endurance of the group after the PGR showed significantly higher values as compared with the groups. Conclusion: The group after anthropometric PGR showed higher muscular endurance and ratios compared with the during and before PGR groups.
Comparison of flexibility and local muscular endurance of teenagers in different growth rate peaks
Keywords: Adolescent health; Growth; Physical fitness